Column Selection for Biomedical Analysis Supported by Column Classification Based on Four Test Parameters - Plenis, Alina (Int J Mol Sci, 2016)
This article focuses on correlating the column classification obtained from the method created at the Katholieke Universiteit Leuven (KUL), with the chromatographic resolution attained in biomedical separation. In the KUL system, each column is described with four parameters, which enables estimation of the F(KUL) value characterising similarity of those parameters to the selected reference stationary phase. Thus, a ranking list based on the F(KUL) value can be calculated for the chosen reference column, then correlated with the results of the column performance test. In this study, the column performance test was based on analysis of moclobemide and its two metabolites in human plasma by liquid chromatography (LC), using 18 columns. The comparative study was performed using traditional correlation of the F(KUL) values with the retention parameters of the analytes describing the column performance test. In order to deepen the comparative assessment of both data sets, factor analysis (FA) was also used. The obtained results indicated that the stationary phase classes, closely related according to the KUL method, yielded comparable separation for the target substances. Therefore, the column ranking system based on the F(KUL)-values could be considered supportive in the choice of the appropriate column for biomedical analysis.